2019
DOI: 10.31557/apjcp.2019.20.7.2117
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activities of Ricin-Liposome Complexes on SKMEL-28 Cells

Abstract: Background: Ricin has been reported as a potential chemical for cancer treatment. However, so far, the application of ricin in cancer treatment is very limited because of its non-specificity. Methods: In this study, ricin were conjugated/ encapsulated with DOTAP/DOPE liposome to form ricin-liposome complexes (ricin-lipososme1, ricin-liposome2, ricin-liposome3 and ricin-liposome4). Characteristics of ricin-liposome complexes were analyzed and their effects on survival, apoptosis, migration, invasion and tumor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…As shown in Figure 1B,C , WT161 suppressed the cell growth of retinoblastoma cell in a dose- and time-dependent manner. In addition, to further investigate the effect of WT161 on suspension cell Y79, we performed the soft agar colony forming assay ( 25 ). As shown in Figure 1D , the results revealed that WT161 inhibits the colony formation of Y79 cells in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1B,C , WT161 suppressed the cell growth of retinoblastoma cell in a dose- and time-dependent manner. In addition, to further investigate the effect of WT161 on suspension cell Y79, we performed the soft agar colony forming assay ( 25 ). As shown in Figure 1D , the results revealed that WT161 inhibits the colony formation of Y79 cells in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…At first, the standard curves were prepared. For example, the BSA solutions with different concentrations (10,20,25,50,75, 100, and 150 μg/mL) were configured, then 10 μL of each BSA solution was pipetted into the 96-well plates, and then 200 μL of the Coomassie Plus Reagent was added to each well (each group of three parallel samples). The mixtures were shaken for 30 s and then incubated for 10 min at room temperature.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In addition to assisting in the effective delivery of anticancer drug, some proteins are also used as tumor treatment drugs due to their therapeutic effects without chemotherapeutic drug resistance, such as ricin, acacia toxin (abrin), mistletoe phytohemagglutinin (mistletoe lectin), modeccin toxin, and so on. , Ricin, composed of two polypeptide chains A and B, is a plant protein extracted from castor bean seeds, it is a ribosome-inactivating protein that can destroy ribosomes, and also can act on nuclear DNA to induce cancer cell apoptosis to exert its anti-cancer effect. , In addition, the efficiency of ricin is extremely high; the toxic active polypeptide chain can inactivate 2000 ribosomes per minute; only a very small dose can achieve obvious effects in cancer treatment; , and it is a potential drug for cancer therapy. The mechanism, which targets different organelles in cancer cells and triggers different apoptosis pathways, is more attractive than conventional chemotherapy and provides a new route for solving the problem of drug resistance in cancer cells. , …”
Section: Introductionmentioning
confidence: 99%
“…To combat this issue, some strategies such as chemical modification, inhibition, or removal of chain B have been proposed. Instances of the last option include the addition of an anti-tumor antibody (Kanellos et al, 1989;Masui et al, 1989;Li et al, 2016), liposome (Tyagi and Ghosh, 2011;Loan et al, 2019), nanocarrier (Nicolson and Poste, 1978), or fusion protein (O'Hare et al, 1990) to chain A in the absence of chain B.…”
Section: Introductionmentioning
confidence: 99%